Comparing Postoperative Fentanyl Use: Ibuprofen VS Ibuprofen-Dexamethasone as Preemptive Analgesia - Herman, Awanda; Hidayat, Nopian; Sukiandra, Riki; Johannas (Frontiers on Healthcare Research, 2025)
Background: Fentanyl is the most frequently used opioid analgesic for managing postoperative pain. While effective, it is associated with various side effects. Postoperative pain is mainly due to acute tissue damage. Several studies have shown that administering preemptive analgesia before anesthesia can help reduce postoperative pain, thus decreasing the need for fentanyl and its side effects. Methods: This research employed a randomized controlled trial (RCT) with a double-blind design. Postoperative pain was measured using the Numeric Rating Scale (NRS). Patients with an NRS score above 6 received fentanyl. Statistical analysis was conducted to compare the impact of preemptive analgesia with Ibuprofen 800 mg alone versus Ibuprofen 800 mg combined with Dexamethasone 10 mg in patients undergoing postoperative gynecological abdominal surgery. Results: The findings revealed a significant difference in NRS pain scores between the groups. The group receiving the combination of Ibuprofen 800 mg and Dexamethasone 10 mg had a 69% reduction in the need for postoperative fentanyl compared to the group that received only Ibuprofen. Conclusion: Patients who received preemptive analgesia with Ibuprofen and Dexamethasone had lower pain scores and a reduced need for fentanyl in the postoperative period compared to those receiving Ibuprofen alone.